Quick returns, sleep, sleepiness and stress - An intra-individual field study on objective sleep and diary data - Kristin Öster; Philip Tucker; Marie Söderström; Anna Dahlgren (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVES: Quick returns (<11 hours of rest between shifts) have been associated with shortened sleep length and increased sleepiness, but previous efforts have failed to find effects on sleep quality or stress. A shortcoming of most previous research has been the reliance on subjective measures of sleep. The aim of this study was to combine diary and actigraphy data to investigate intra-individual differences in sleep length, sleep quality, sleepiness, and stress during quick returns compared to day-day transitions. METHODS: Of 225 nurses and assistant nurses who wore actigraphy wristbands and kept a diary of work and sleep for seven days, a subsample of 90 individuals with one observation of both a quick return and a control condition (day-day transition) was extracted. Sleep quality was assessed with actigraphy data on sleep fragmentation and subjective ratings of perceived sleep quality. Stress and sleepiness levels were rated every third hour throughout the day. Shifts were identified from self-reported working hours. Data was analyzed in multilevel models. RESULTS: Quick returns were associated with 1 hour shorter sleep length [95% confidence interval (CI) -1.23- -0.81], reduced subjective sleep quality (-0.49, 95% CI -0.69- -0.31), increased anxiety at bedtime (-0.38, 95% CI -0.69- -0.08) and increased worktime sleepiness (0.45, 95%CI 0.22- 0.71), compared to day-day transitions. Sleep fragmentation and stress ratings did not differ between conditions. CONCLUSIONS: The findings of impaired sleep and increased sleepiness highlight the need for caution when scheduling shift combinations with quick returns.